Regulatory role of microRNA in mesenteric lymph nodes after Salmonella Typhimurium infection - Claros-Díaz, Manuel Gonzalo; Herrera‐Uribe, Juber; Zaldívar‐López, Sara; Anaya-Aguilar, Carmen; Luque, Cristina; Bautista-Moreno, Rocío; Carvajal, Ana; Garrido, Juan José (Veterinary Research, 2018)
Salmonellosis is a gastrointestinal disease caused by non‐typhoidal Salmonella serovars such as Salmonella Typhimu‐ rium. This pathology is a zoonosis, and food animals with subclinical infection constitute a vast reservoir for disease. After intestinal colonization, Salmonella Typhimurium reaches mesenteric lymph nodes (MLN), where infection is controlled avoiding systemic spread. Although the molecular basis of this infection has been extensively studied, little is known about how microRNA (miRNA) regulate the expression of proteins involved in the Salmonella‐host interac‐ tion. Using small RNA‐seq, we examined expression profiles of MLN 2 days after infection with Salmonella Typhimu‐ rium, and we found 110 dysregulated miRNA. Among them, we found upregulated miR‐21, miR‐155, miR‐150, and miR‐221, as well as downregulated miR‐143 and miR‐125, all of them previously linked to other bacterial infections. Integration with proteomic data revealed 30 miRNA potentially regulating the expression of 15 proteins involved in biological functions such as cell death and survival, inflammatory response and antigenic presentation. The inflamma‐ tory response was found increased via upregulation of miRNA such as miR‐21 and miR‐155. Downregulation of miR‐ 125a/b, miR‐148 and miR‐1 were identified as potential regulators of MHC‐class I components PSMB8, HSP90B1 and PDIA3, respectively. Furthermore, we confirmed that miR‐125a is a direct target of immunoproteasome component PSMB8. Since we also found miR‐130 downregulation, which is associated with upregulation of HSPA8, we suggest induction of both MHC‐I and MHC‐II antigen presentation pathways. In conclusion, our study identifies miRNA that could regulate critical networks for antigenic presentation, inflammatory response and cytoskeletal rearrangements.
Keywords: Salmonelosis; MicroRNA; Small RNA‐seq; Salmonellosis; Salmonella‐host interaction; Immunoproteasome